Karakteristik Warna Pada Lukisan Wakidi - Alfiqra Aswat; Rajudin Rajudin; Rica Rian (V-art: Journal of Fine Art, 2021)
This study discusses the color character that Wakidi presents in his paintings, which mostly uses soft colors in his naturalist paintings. The method used in this study refers to a qualitative method which includes field observations, interviews, documentation, and literature studies as well as research conducted in the Padang area, West Sumatra. Based on the results of research on the characteristics of Wakidi's color in his paintings, the use of soft colors in Wakidi's paintings is to remind him that nature is very beautiful and has a calm atmosphere. Based on the type of human according to the typology of Hypocrates and Galenus Wakidi, it is a Phlegmatic type. Wakidi tends to present natural scenery in the evening with a reddish color. The color characters in Wakidi's works are discussed based on color dimensions, color composition, and differences with other artists. There is a lot that can be learned and researched from Wakidi's active work in addition to being a painting teacher and an Mooi Indie artist at the beginning of the pioneering of fine arts in West Sumatra, as well as being able to become a cultural asset that elevates natural scenery and ancient culture into his paintings. It is hoped that research on the color character of Wakidi's paintings can be a reference so that there are opportunities for other researchers to research from other scientific points of view.